Investigation of dynamic fracture behavior and energy dissipation of water-bearing coal under impact load. (November 2022) - Gong, Shuang; Zhou, Lei; Wang, Wen; Wang, Chaofei
Highlights: Water-saturated coal samples have a higher sensitivity to dynamic fracture toughness than dry coal samples to loading air pressure. It is easier to create induced fractures to form complex fracture networks when the coal sample remains dry. The fracture energy of water-bearing coal samples shows an exponential increase with loading pressure. Abstract: The stability of residual coal pillar in coal mine is significantly affected by the ponding in goaf and the dynamic disturbances such as blasting vibration and mine tremor activity in the production process of surrounding coal mines. In this paper, the effects of different loading pressure and water-bearing state on the dynamic fracture mechanical properties and energy dissipation law of coal samples were studied. The dynamic fracture characteristics of dry, natural and water-saturated notched semi-circular bending (NSCB) coal samples were tested under different loading pressure by using the impact loading system of split Hopkinson pressure bar (SHPB). A high-speed camera was used to record the dynamic crack propagation process. Combined with image processing method and fractal dimension calculation software, the influence of loading pressure and water-bearing state on fractal characteristics of crack propagation in coal specimens was further analyzed. The results show that at the beginning of crack initiation, water-saturated coal samples are easy to fracture compared to dry and natural coal samples. During the crack propagation, the dry and natural coal samples have a shorter crack penetration time compared to the water-saturated samples. The fracture toughness of the saturated coal sample is sensitive to the loading pressure and there is a threshold value. When the loading pressure is lower than 0.483 MPa, the dynamic fracture toughness of the dry coal sample is greater than the saturated coal sample. While the loading pressure is higher than 0.483 MPa, the dynamic fracture toughness of the saturated coal sample is greater than the dry coal sample. The fractal dimension of the crack propagation path of the coal sample changed as a "V" shape with the loading pressure. The fractal dimension of the crack propagation path of the dry coal sample is always higher than the water-saturated coal sample. The fracture energy of the coal sample meets the y = a · b x exponential growth relationship with the loading pressure. The fracture energy of water-saturated coal sample is the largest and the natural state is the least during the fracture process. The research results can provide theoretical guidance for the stability assessment of residual coal pillar as well as the safe and efficient mining of deep coal resources.